Wild Medicinal Plants of Jaunsar-Bawar (Western Himalayas) Uttaranchal - I - Singh, Dhan; Pundir, Y. P. S. (Indian Forester, 2004)
The paper reports fifty wild medicinal plants used by the natives of Jaunsar-Bawar , Western Himalayas , Uttaranchal.